HASE HAWAKA TRADITION AT SMA NEGERI 1 WEST MALAKA IN MALAKA REGENCY - Florentina Rika; Nurdin (Sociology Education, Teaching Training and Education Faculty, Muhammadiyah University of Kupang, 2022)
The purpose of this study is to find out the process of carrying out the “hase hawaka” traditional ceremony and to find out the values contained in the “hase hawaka” tradition. The location of this research is SMA Negeri 1 Malaka Barat, Malaka Regency. The study used purposive sampling to select the informants such as teachers and students. Several techniques were used to collect data including interviews and documentation. The data analysis technique used in this research is descriptive qualitative. The results of this study indicate that (1) the process of implementing the “hase hawaka” tradition ceremony at SMA Negeri 1 Malaka Barat to prepare a ceremony when there are guests who come to visit the school. The teachers asked one of the best students at school to welcome guests who come. Prepare a local language to entertain the guest, and dance to welcome guests. This dance will be performed by students, totaling 10 females and plus 2 males. (2) The social values contained in the “hase hawaka” tradition at SMA Negeri 1 Malaka Barat are religious values, politeness values, and cultural values.